Exposure assessment to bisphenol A (BPA) in Portuguese children by human biomonitoring - Correia-Sá, Luísa (2017)
Exposure to bisphenol A (BPA) is known to be widespread and available data suggests that BPA can act as an endocrine disruptor. Diet is generally regarded as the dominant BPA exposure source, namely through leaching to food from packaging materials. The aim of this study was to evaluate the exposure of 110 Portuguese children (4-18 years old), divided in two groups: the regular diet group (n = 43) comprised healthy normal weight/underweight children with no dietary control; the healthy diet group (n = 67) comprised children diagnosed for obesity/overweight (without other known associated diseases) that were set on a healthy diet for weight control. First morning urine samples were collected and total urinary BPA was analyzed after enzymatic hydrolysis via on-line HPLC-MS/MS with isotope dilution quantification. Virtually, all the children were exposed to BPA, with 91% of the samples above the LOQ (limit of quantification) of 0.1 μg/L. The median (95th percentile) urinary BPA levels for non-normalized and creatinine-corrected values were 1.89 μg/L (16.0) and 1.92 μg/g creatinine (14.4), respectively. BPA levels in the regular diet group were higher than in the healthy diet group, but differences were not significant. Calculated daily BPA intakes, however, were significantly higher in children of the regular diet group than in children of healthy diet group. Median (95th percentile) daily intakes amounted to 41.6 (467) ng/kg body weight/day in the regular diet group, and 23.2 (197) ng/kg body weight/day in the healthy diet group. Multiple logistic regression analysis revealed that children in the healthy diet group had 33% lower intakes than children in the regular diet group (OR 0.67; 95% CI 0.51-0.89). For both groups, however, urinary BPA levels and daily BPA intakes were within the range reported for other children's populations and were well below health guidance values such as the European Food Safety Authority (EFSA) temporary tolerable daily intake (t-TDI) of 4 μg/kg body weight/day. In addition, lower daily BPA intakes were more likely linked with the inherent dietary approach rather than with high BMI or obesity.